KETERLIBATAN PEREMPUAN DALAM NAFKAH KELUARGA PERSPEKTIF AL-QUR’AN - Ainun Dwi Hamdani; Aisyah Arsyad (Universitas Islam Negeri Alauddin Makassar, 2022)
This paper discusses the involvement of women in family support and its review in the qur’anic perspective. This study is a result of field research using an exegesis interpretive (tafsir) and a gender approach. The results of this study indicate that women's involvement in providing for the family is due to economic limitations and as a form of women's existence in society. Women who work adhering to religious values ​​about family life that support each other are formed from the prevailing religious structures in their environment, namely in the religious traditions they adhere to and carry out such as monthly routine studies or other religious traditions, for example in reading Surah Yasin and tausiyah on Friday nights. The perception of women who provide for their families still believes that providing a living is not the wife's obligation but is still the husband's obligation. For women in Lalebata village always maintain good intentions in helping the family's economy and still pay attention to the rules set by religion in order to minimize the negative impacts that can trigger rifts in the household.